A nuclease-polymerase chain reaction enables amplification of probes used for capture-based DNA target enrichment - Leong, Ka Wai (Nucleic Acids Res, 2019)
DNA target enrichment via hybridization capture is a commonly adopted approach which remains expensive due in-part to using biotinylated-probe panels. Here we provide a novel isothermal amplification reaction to amplify rapidly existing probe panels without knowledge of the sequences involved, thereby decreasing a major portion of the overall sample preparation cost. The reaction employs two thermostable enzymes, BST-polymerase and duplex-specific nuclease DSN. DSN initiates random ‘nicks’ on double-stranded-DNA which enable BST to polymerize DNA by displacing the nicked-strand. Displaced strands re-hybridize and the process leads to an exponential chain-reaction generating biotinylated DNA fragments within minutes. When starting from single-stranded-DNA, DNA is first converted to double-stranded-DNA via terminal-deoxynucleotidyl-transferase (TdT) prior to initiation of BST–DSN reaction. Biotinylated probes generated by TdT–BST–DSN (TBD) reactions using panels of 33, 190 or 7186 DNA targets are used for hybrid-capture-based target enrichment from amplified circulating-DNA, followed by targeted re-sequencing. Polymerase-nuclease isothermal-chain-reactions generate random amplified probes with no apparent sequence dependence. One round of target-capture using TBD probes generates a modest on-target sequencing ratio, while two successive rounds of capture generate >80% on-target reads with good sequencing uniformity. TBD-reactions generate enough capture-probes to increase by approximately two to three orders-of-magnitude the target-enrichment experiments possible from an initial set of probes.